36.6k views
4 votes
Solve by substitution.
3x-y=5
-2x+y=0

User Ksasq
by
5.9k points

2 Answers

4 votes
First, rewrite the equation -2x+y=0 into y-mx+b format. This is y=2x+0. We can then substitute this into our first equation.
3x-y=5
turns into
3x-2x=5
x=5
We can then plug in our value for x to find y.
3(5)-y=0
simplifies into
15-y=0
Simplify this to get that y=15
You can then plug these into the other equation ot make sure it's right.
-2(5)+15=5
-10+15=5
which is 5=5 (true)

So your answers are x=5 and y=15.

:)
User Lyra Orwell
by
5.8k points
4 votes
In order to use substitution, you need to isolate a variable on one of the equations:

-2x+y=0
y=2x

Then you plug that equation into the other equation. Since we isolated y, we plug in 2x for y in the other equation:

3x-(2x)=5
x=5

Then plug the value you found into any equation to solve for the other variable:

3(5)-y=5
15-y=5
-y=-10
y=10

So your answers are x=5, y=10
User Ricard Kollcaku
by
6.1k points